Grunt to historia? Vicente Luis Mora i jego "Centroeuropa" (2020) jako metapowieść intrahistoryczna - Marta Eloy Cichocka (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria, 2023)
The purpose of the essay is to introduce the figure of a contemporary Spanish author, Vicente Luis Mora, and his novel Centroeuropa to the Polish literary researchers, as well as to analyze the special character of this novel in terms of reading agreement and the most adequate terminology concerning the literary genre, to which it belongs, based on the form oftypological characteristics of a novel that includes ten essential points: paratext, plot, narration, time structure, poetics, the question of mimesis, the loyalty of history towards History, metatextuality, ideological character and the strategies used by the author. On the basis of these reflections it can be concluded that Centroeuropa by Vicente Luis Mora is a metanovel about a man who is looking for his way in a breakthrough moment in the history of Europe, between the 18th and 19th century, in the declining feudal‑absolutist Prussia and the emerging liberal‑capitalist Prussia, in the embryonic society, where economic and political norms haven’t been fully constructed yet and women are not full‑fledged members of society. Centroeuropa is a multi‑dimensional novel inspired by the past of Central Europe, but – above all – a metanovel about writing and its servitude.